Design and rapid prototyping of a closed-loop control strategy of the injected mass for the reduction of CO2, combustion noise and pollutant emissions in diesel engines. (15th December 2018) - Ferrari, A.; Novara, C.; Paolucci, E.; Vento, O.; Violante, M.; Zhang, T.
Highlights: An innovative closed-loop control strategy of the injected mass has been developed. The strategy has been implemented in rapid prototyping hardware. The performance of the new injection system has been compared with that of a standard CR. The potential of the strategy to reduce CO2, CN and pollutants has been assessed. Abstract: A closed-loop strategy that is capable of controlling the fuel injected mass in the combustion chamber of a Common Rail diesel engine has been set up. The pressure time histories measured along the rail-to-injector pipe have been used to evaluate the instantaneous mass flow-rate entering the injector. This flow-rate has then been integrated between two time instants, and the thus calculated fuel mass has resulted to correlate well with the injected mass. A rapid prototyping hardware has been realized to control the rail pressure and the injected mass through feedback strategies. Steady state and dynamic tests on the prototypal injection system have been carried out on a hydraulic rig. The innovative injection apparatus, which features the closed-loop control of the injected mass, can significantly improve the injected mass accuracy for the different thermal regimes, compared to a state-of-the-art Common Rail system. The error in the actuated injected mass was found to be below 1 mg for all the working conditions and the sensitivity of the injection performance to fuel temperature was significantly reduced. Furthermore, the dynamic response of the new injection system to either step or ramp transients in the rail pressure and in the injected mass was also enhanced appreciably. This has allowed the calibration maps to be followed more precisely during the engine transients. Preliminary simulation tests, performed with a 1D code on a diesel engine for light duty commercial vehicles, have proved that the new technology could lead to important reductions in the CO2 engine out emissions (3%) and in the combustion noise (up to 0.5 dBA). Significant percentage improvements in NOx (3%) and soot (6%) engine out emissions have also been found.